PENERAPAN METODE UMMI DALAM PEMBELAJARAN AL-QUR’AN - Didik Hernawan; Muthoifin Muthoifin (Profetika: Jurnal Studi Islam, 2018)
This study aims to describe and compare the implementation of Quran learning usingthe Ummi method, the results of student achievement in the application of Ummi method, the advantages and weakness of Ummi method in the ElementarySchool Daar El-Dzikir Sukoharjo and the Islamic Elementary School Integrated Insan Kamil Karanganyar. This research is included in qualitative research by describing the data collected as the scope of research and the field as a place of research (field research). The nature of this study is more in the direction of comparative study research with data collection techniques in the form of interviews that are validated by observation, and documentation. The results of research from this study are the application ofUmmi method in learning of the Quran at SDU Daar El-Dzikir and SDIT Insan Kamil by using ten pillars that have been formulated by the Ummi Foundation. The ten Pillars are goodwill management, teacher certification, stages of good and right, clear and measurable targets, consistent mastery learning, adequate time, proportional teacher and student ratios, internal and external controls, progress reports of each student and a reliable coordinator. The application of the ten pillars of Ummi method at SDU Daar El-Dzikir and SDIT Insan Kamil is different in determining targets, adding training time (driling), teacher and student ratios, student progress reports, and internal controls. The results of student achievement in the application of Ummi method are measured from students who have passed the exam by completing the reading material. Students are able to read Quran with tartil and fasahah. SDU Daar El-Dzikirhas graduated 89 students for three examinations. While SDIT Insan Kamil has passed 87 students for two examinations. The advantages of Ummi method are qualitybased systems, systematic stages, continuous material, and strict control. The weakness ofUmmi method is needed a lot of teachers, a long time and a large cost.Penelitian ini bertujuan untuk mendeskripsikan dan membandingkan pelaksanaan pembelajaran al-Qur’an dengan menggunakan metode Ummi, hasil pencapaian siswa dalam penerapan metode Ummi, kelebihan dan kekurangan metode Ummi di Sekolah Dasar Unggulan Daar El-Dzikir Sukoharjo dan Sekolah Dasar Islam Terpadu Insan Kamil Karanganyar. Penelitian ini termasuk dalam penelitian kualitatif dengan menjabarkan data-data yang terkumpul sebagai ruang lingkup penelitiannya danlapangan sebagai tempat penelitiannya (field research).Sifat dari penelitian ini lebih ke arah pada penelitian studi komparasi dengan teknik pengumpulan data berupa wawancara yang divalidasi dengan observasi, dan dokumentasi. Hasil penelitian ini adalah penerapan metode Ummi dalam pembelajaran al-Qur’an di SDU Daar El-Dzikir dan SDIT Insan kamil dengan menggunakan sepuluh pilar yang telah dirumuskan oleh Ummi Foundation yaitu goodwill manajemen, sertifikasi guru, tahapan baik dan benar, target jelas dan terukur,mastery learning yang konsisten, waktu memadai , rasio guru dan siswa yang proporsional, kontrol internal dan eksternal, progress report setiap siswa dan koordinator yang handal.Penerapan sepuluh pilar metode Ummi di SDU Daar El-Dzikir dan SDIT Insan Kamil berbeda dalam penentuan target, penambahan waktu latihan (driling), rasio guru dan siswa, progress report siswa, dan kontrol internal. Hasil pencapaian siswa dalam penerapan metode Ummi diukur dari siswa yang telah dinyatakan lulus ujian dan melaksanakan khataman dengan menyelesaikan jilid 1 sampai jilid tajwid sehingga menguasai tartil dan fasahah. SDU Daar El-Dzikir telah meluluskan 89 siswa selama tiga kali khataman. Sedangkan SDIT Insan Kamil sudah meluluskan 87 siswa selama dua kali khataman. Kelebihan metode Ummi yaitu sistem yang berbasis mutu, tahapan yang sistematis, materi yang kontinu, dan kontrol yang ketat. Kelemahan metode Ummi yaitu membutuhkan guru yang banyak, waktu yang lama dan biaya yang besar.